Design and Implementation of a Detection and Diagnostic System for Anomalies in a Grid-Connected Photovoltaic System - Kani Mboyo, Ursula Vanelie; Mankiti Fati, Aristide; Samba, Rene (European Scientific Journal, ESJ, 2026)
This paper presents the design and implementation of a detection and diagnostic system for anomalies in a photovoltaic installation connected to the national EEC grid in Congo Brazzaville, within the framework of Denis SASSOU NGUESSO University. The main objective is to reduce maintenance costs and improve the energy productivity of the plant, considering that photovoltaic systems are inherently subject to operational failures. The study focuses on faults affecting the PV generator and proposes a method for detecting and locating anomalies that lead to reduced production. The approach is based on the analysis of the I–V characteristics of the PV generator under different operating modes. The results show that the Lambert W/numerical model accurately reproduces the electrical behavior of the module, with low and unbiased errors. This model provides a solid foundation for supervision applications, enabling performance drift detection, loss identification, and operating point optimization, thereby ensuring reliability and efficiency in photovoltaic system monitoring.